Abya Yala and the Andean worldview - Carhuapoma Gamboa, Angelica (2024)
The objective of this work is to understand and reflect upon Abya Yala and the Andean worldview, which underwent a cultural development different from the Western one, interrupted by the Spanish invasion that imposed its language,customs and god. The term Abya Yala is designated to the American continent by the Kuna people, accepted by the organization of indigenous peoples, and carries the meaning of "Land in full maturity” or “Land of vital blood." The worldview of these peoples was marked by the  conservation of nature, as they considered themselves part of it. Thisstarting point establishes a harmonious relationship between inhabitants and nature. We conclude that Andean peoplesare in a process of reconstructing the Andean worldview, valuing their tradition, language, and ancestral customs, in the face of the imposition of a dominant Eurocentric worldview that attempted to strip away our ancestral knowledge and wealth.